Comparative Effect of Leguminous and Non-Leguminous Green Manure Crops on Soil Properties at Rampur, Chitwan, Nepal - Mukesh Pant; Swikriti Panthi; Roshan Chand; Toran Devkota; Ranjan Bhattarai (Turkish Journal of Agriculture: Food Science and Technology, 2025)
Green manuring is the practice of adding cover crops to the soil. The excessive use of chemical fertilizers, intensive farming, faulty cultivation practices, and poor soil management have degraded soil health, necessitating the use of green manure. This study aimed to evaluate the best-performing green manuring crops that enhance soil properties from the first week of April to the first week of July in Rampur, Chitwan, Nepal. The experiment was performed under Randomized complete block design (RCBD) with five treatments and four replications. The treatments were cowpea (Vigna unguiculata L.), black gram (Vigna mungo L.), Sesbania (Sesbania aculeata Wild.), mung bean (Vigna radiata L.) and Sudan grass (Sorghum bicolor L.). The biomass yield, soil pH, bulk density, soil organic matter, Total nitrogen, and available phosphorus were measured. The data were analyzed using R-Studio for mean comparison among significant variables using Duncan’s Multiple Range Test (DMRT) at a 5% significance level. Sesbania consistently enriched the soil with higher total nitrogen (0.197%), available phosphorus (11.36 kg/ha), soil organic carbon (2.29%), soil carbon stock (40.70 t/ha), low bulk density (1.20 g/cm³), fresh biomass yield (8.25 t/ha), and dry biomass yield (1.62 t/ha). Cowpea emerged as a reliable alternative when Sesbania was not available. However, mung bean and black gram lagged in biomass production and nutrient addition. Sudan grass performed poorly, contributing the least organic matter and available phosphorus. Sesbania, therefore, stands out as the optimal choice, while cowpea serves as a viable substitute when sesbania is unavailable. In addition, leguminous green manuring crops outperformed non-leguminous crops.